Anterior mediastinal mass in a breast cancer patient mimicking lymphadenopathy: a case report - Soumya El Graini; Sara Habib Chorfa; Hamza Retal; Driss El Alaoui; Youssef Mahdi; Basma El Khannoussi; Youssef Omor; Rachida Latib; Sanae Amalik (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background The mediastinum is an anatomical region containing vascular, visceral, and osseous structures. In case of mediastinal masses in the prevascular space, the mnemonic word "4T" helps to group the most common etiologies, namely thyroid pathology, thymoma and its variants, the "terrible" lymphoma, and teratoma. In oncologic patients, the main differential diagnosis is metastatic lymphadenopathy and one should be careful when analyzing this condition. Case presentation We present the case of a 54-year-old woman with a history of thyroidectomy who was found to have multiple anterior mediastinal masses during a breast cancer evaluation. Initial concerns about metastatic lymphadenopathy were ruled out after imaging showed no connection to the cervical thyroid gland, and a biopsy confirmed the masses as benign ectopic thyroid tissue. Given the patient’s stable condition and preference, conservative management with close monitoring was chosen instead of surgery. Conclusions The case underscores the rarity and diagnostic challenges of anterior mediastinal mass, especially in oncology, highlighting the crucial role of CT imaging in identifying and characterizing those masses, aiding in differential diagnosis and guiding appropriate management strategies.